(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Over the last several decades, risk supervision has been a hot subject in both academic world and practice. The complexity of the company and the environment inwhich it works determine operational risk. As the company or the environment becomes more dynamic, i.e., where change is a constant characteristic and a factor to consider into the management of the firm, such complexity grow. The important issue companies react to such changes today, and what measures can businesses take to anticipate and prepare for change as the nature of business and the environment becomes more dynamic. The majority of business intelligence (BI) programs or software have been utilized to improve risk supervision, and business intelligence methods have improved risk management solutions. This introductory paper offers an overview of current business intelligence research in risk management.